Polymerized-complex method for preparation of supported bimetallic alloy and monometallic nanoparticles. Issue 14 (19th January 2016) - Li, Pingyun; Li, Fengsheng; Deng, Guodong; Guo, Xiaode; Liu, Hongying; Jiang, Wei; Wang, Tianhe
Abstract : Herein, we report a novel polymerized complex method for preparation of Ni–Pd, Ni–Pt, Cu–Pt alloy, Pt, Pd, Ag, Ni, Cu nanoparticles. The grain sizes and crystalline phases of these nanoparticles can be controlled. Abstract : Herein, we report a novel polymerized-complex method for the preparation of Ni–Pd, Ni–Pt, and Cu–Pt alloys and Pt, Pd, Ag, Ni, and Cu nanoparticles. The grain sizes and crystalline phases of these nanoparticles can be controlled. These nanoparticles are obtained via the formation of a polymerized complex and release of reducing gases during N2 -protected calcination.